The Influence of Adiposity Levels on the Relation between Perfluoroalkyl Substances and High Depressive Symptom Scores in Czech Adults - Neto, Geraldo; Bobak, Martin; Gonzalez-Rivas, Juan P; Klanova, Jana (Toxics, 2023)
The extensive use and bioaccumulation of Perfluoroalkyl Substances (PFAS) over time raise concerns about their impact on health, including mental issues such as depression. This study aims to evaluate the association between PFAS and depression. In addition, considering the importance of PFAS as an endocrine disruptor and in adipogenesis, the analyses will also be stratified by body fat status. A cross-sectional study with 479 subjects (56.4% women, 25-89 years) was conducted. Four PFAS were measured: perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), and perfluorooctane sulfonate (PFOS). The Poisson regression model was applied using robust error variances. The fully adjusted model included age, sex, educational level, income, smoking, physical activity, body fat percentage, and the questionnaire to assess depression. The prevalence of depression and high body fat was 7.9% and 41.1%, respectively. Only PFOA was significantly associated with depression in the entire sample (prevalence rate (PR): 1.91; confidence interval (CI95%): 1.01-3.65). However, in the group with normal adiposity, PFOA (3.20, CI95%: 1.46-7.01), PFNA (2.54, CI95%: 1.29-5.00), and PFDA (2.09, CI95%: 1.09-4.00) were also significant. Future research should investigate the role of obesity as well as the biological plausibility and possible mechanisms increasing the limited number of evidences between PFAS and depression.
Keywords: depression; PFDA; PFNA; PFOA; body fat; PFOS; adults; perfluoroalkyl substances